2001
DOI: 10.1021/la001226i
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Evaluation of Nanoparticles Assembled from Poly(lactic acid)−Poly(ethylene glycol) (PLA−PEG) Block Copolymers as Drug Delivery Vehicles

Abstract: Nanoparticles assembled from poly(D,L-lactic acid)-poly(ethylene glycol) (PLA-PEG) block copolymers may have a therapeutic application in site-specific drug delivery. A series of AB block copolymers based on a fixed PEG block (5 kDa) and a varying PLA segment (2-110 kDa) have been synthesized by the ring-opening polymerization of D,L-lactide using stannous octoate as a catalyst. These copolymers assembled to form spherical nanoparticles in aqueous media following precipitation from a water-miscible organic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
177
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(199 citation statements)
references
References 45 publications
19
177
1
2
Order By: Relevance
“…57 The size of mPEG-PLA nanoparticles prepared with constant PEG 5000 was found to increase with the PLA block molecular weight. 59 With mPEG 5000 -PLA 2000-30000 nanoparticle diameters (from 26 to 64 nm in diameter) were shown to be independent of the copolymer concentration in the organic phase, whereas with higher PLA block molecular mass (45,000 Da) nanoparticle size was dependent on the copolymer concentration in the organic phase. 59 After preparation, nanoparticles can be freezedried in the presence of appropriate cryoprotector for longterm preservation.…”
Section: Nanoparticle Preparationmentioning
confidence: 92%
See 3 more Smart Citations
“…57 The size of mPEG-PLA nanoparticles prepared with constant PEG 5000 was found to increase with the PLA block molecular weight. 59 With mPEG 5000 -PLA 2000-30000 nanoparticle diameters (from 26 to 64 nm in diameter) were shown to be independent of the copolymer concentration in the organic phase, whereas with higher PLA block molecular mass (45,000 Da) nanoparticle size was dependent on the copolymer concentration in the organic phase. 59 After preparation, nanoparticles can be freezedried in the presence of appropriate cryoprotector for longterm preservation.…”
Section: Nanoparticle Preparationmentioning
confidence: 92%
“…59 With mPEG 5000 -PLA 2000-30000 nanoparticle diameters (from 26 to 64 nm in diameter) were shown to be independent of the copolymer concentration in the organic phase, whereas with higher PLA block molecular mass (45,000 Da) nanoparticle size was dependent on the copolymer concentration in the organic phase. 59 After preparation, nanoparticles can be freezedried in the presence of appropriate cryoprotector for longterm preservation. 51,62,63 Pegylated nanoparticle structure Nanoparticles prepared from mPEG-PLA/PLGA copolymers are constituted of a PLA/PLGA hydrophobic core surrounded by a hydrophilic PEG corona or outer shell.…”
Section: Nanoparticle Preparationmentioning
confidence: 92%
See 2 more Smart Citations
“…The approximate micelle aggregation number (N agg ) can be calculated from the ratio of the average molecular weight of the micelle to the molecular weight of the block copolymer [14,15,16]. Dynamic Light Scattering experiments indicated that the average molecular weight of the micelle is ∼ 4.6×10 4 Dalton.…”
Section: Fluorescent Dye Encapsulation and Release From Polymeric Micmentioning
confidence: 99%